Eye transformer is a negative regulator of Drosophila JAK/STAT signaling. - Kallio, J.; Myllymäki, H.; Grönholm, J.; Armstrong, M.; Vanha-aho, L.M.; Mäkinen, L.; Silvennoinen, O.; Valanne, S.; Rämet, M. (FASEB Journal (Federation of American Societies for Experimental Biology), 2010)
JAK/STAT signaling pathway is evolutionarily conserved and tightly regulated. We carried out a reporter-based genome-wide RNAi in vitro screen to identify genes that regulate Drosophila JAK/STAT pathway and found 5 novel regulators. Of these, CG14225 is a negative regulator structurally related to the Drosophila JAK/STAT pathway receptor Domeless, especially in the extracellular domain, and to the mammalian IL-6 receptor and the signal transducer gp130. CG14225 coimmunoprecipitates with Domeless and its associated kinase hopscotch in S2 cells. CG14225 RNAi caused hyperphosphorylation of the transcription factor Stat92E in S2 cells on stimulation with the Drosophila JAK/STAT pathway ligand unpaired. CG14225 RNAi in vivo hyperactivated JAK/STAT target genes on septic injury and enhanced unpaired-induced eye overgrowth, and was thus named the eye transformer (ET). In the gastrointestinal infection model, where JAK/STAT signaling is important for stem cell renewal, CG14225/ET RNAi was protective in vivo. In conclusion, we have identified ET as a novel negative regulator of the Drosophila JAK/STAT pathway both in vitro and in vivo, and it functions in regulating Stat92E phosphorylation.